Resiliensi Ekonomi Keluarga Perspektif Fikih: Studi Kasus Peran Pedagang Perempuan di Pasar Campurejo Kota Kediri Dalam Mencari Nafkah - M. Mubasysyarum Bih; Ahmad Badi' (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aims to describe the activities of women traders in the Campurejo market, Mojoroto Kediri City in their resilience to maintain their family's food security, using a fiqh perspective. This research uses a qualitative approach of field research type. This study found that there is no prohibition in Islam for women traders to play a role in the public sector to earn a living, because the work of trading in the market is carried out in harmony with the principles of sharia, maintaining ethics and honor, and not to make her neglect her children and obligations at home; such as serving food and so on.